O mercado de capitais e os círculos de informações financeiras no território brasileiro - André Pasti; Adriana Maria Bernardes da Silva (Confins)
This paper discusses the movement of stock markets in the financialization of the Brazilian territory, through the analysis of the circuits of financial information underlying the functioning of this market in the period of globalization. To this end, we discuss the relations between the circles of information and the new uses of the territory, the main technical and political transformations in the Brazilian capital markets from globalization, new agents and contents brought by circles of financial information in São Paulo and the implications of this reorganization of the capital market to Brazilian urban network.